Teacher Preparation Based on Competencies: Reality and Aspirations (Journal of human and social sciences, 2016)
The aim of this research is to identify the reality of teacher preparation in Libya. To collect, analyze, and understand the problem under study, the researchers employed the descriptive method, conducting a survey of studies presented in the Libyan Arab society in the field of teacher preparation. The research led to a number of conclusions, the most important of which are the following: most teachers have not reached the required level of proficiency in many competencies, such as lesson planning and implementation, classroom management, communication skills, and others. This may be attributed to the weakness of their preparation process, which leads us to emphasize the necessity of focusing on teacher preparation in accordance with modern approaches that educational research has proven to be effective.
Keywords: Teacher Preparation; Teaching Competencies; Effective Teaching; Educational Development; Education Reality in Libya